Integrating single-cell RNA sequencing and spatial transcriptomics reveals the therapeutic effect of nitazoxanide in head and neck squamous cell carcinoma - Xiaohua Jiang; Liqi Chen; Zixia Xu; Hangzhe Sun; Jing Ye; Ziyi Guo; Mang Xiao (Discover Oncology)
Abstract Background Head and Neck Squamous Cell Carcinoma (HNSCC) is a prevalent and deadly cancer with limited treatment options, for which autophagy has a dual impact. Nitazoxanide is a broad-spectrum antiviral drug showing promise in treating cancer, but its role in regulating autophagy in HNSCC remains unexplored. Materials and methods The molecular mechanisms were explored through Differential expression analysis, functional enrichment analysis, risk prognostic model, nomogram model, GSEA, GSVA, WGCNA, mutation analysis, scRNA analysis, spatial transcriptomic analysis, and L1000FWD analysis. And the impact of Nitazoxanide was experimentally verified. Results We identified 32 differentially expressed ARGs and 4 hub genes. They are involved in autophagy, apoptosis, and human cytomegalovirus infection. And hub genes were identified as independent prognostic factors for HNSCC. GSEA, GSVA and WGCNA uncovered the role of the dysregulation of IFN-α response pathway in HNSCC. scRNA and spatial transcriptomic analyses revealed the expression models of each hub gene. Furthermore, potential drugs were explored using L1000FWD analysis. Additionally, Nitazoxanide’s function was verified in vitro. Conclusion Our findings established that Nitazoxanide has the potential to play a role in the treatment of HNSCC. We suggested that Nitazoxanide acts on NKX2-3, PINK1, BIRC5 and CDKN2A to inhibit the development of HNSCC through regulating autophagy, and it is a promising candidate drug for HNSCC.